PROFESINALISME MUBALIGH BAGI PERKEMBANGAN DAKWAH - Mutiara cendekia sandyakala (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2019)
Professional muballigh observes the new things in order to follow the flow of globalization, and also can follow the increasing competition due to the progress of science and the development of more advanced age and competitive. Professional appearance constantly changing from year to year with the criteria of performance in accordance with the attitude, personality, and appearance is strongly influenced by the place and the environment where the person carrying out the profession. Da'wa should be able to sharpen the intellect object message. With today's challenges steps to be taken in a preacher or propaganda agencies in order to preach effectively. A professional who is successful in achieving his goal he must prioritize the responsibility to complete the task complete, and create schedules and working to meet the schedule to manage time. Professionals muballigh is an attitude that really shows the master, earnestly and serious profession, perform analysis, understand the work and also the confidence and skills in relating to others and to always perform continuous self-development so as not to abandoned or left behind. A person who has a professional attitude, only those who really have the courage and faith, and God only step that they lean. In addition they are earnest, not easily discouraged, also seriously pursue live, dare mengahapi challenges of the times, practice what is taught by Allah in the Qur'an and as-Sunnah always followed.